HUBUNGAN ANTARA KEMAMPUAN INTERAKSI SOSIAL DENGAN KECERDASAN EMOSIONAL ANAK USIA DINI - annisa eli yana (Universitas Muhammadiyah Metro, 2023)
Based on the results of initial observations in Group B RA Al-Wafi Panyileukan Bandung found a gap between high social interaction skills and low emotional intelligence. It can be seen that children's social interaction skills are no longer awkward in conversing with peers and teachers. However, it is different with children's emotional intelligence, which can be seen from the way they deal with problems which are always accompanied by fights, hostility, selfishness. The approach used in this research is a quantitative approach with correlational research methods. In this study using a total sampling technique because it took all members of the population, namely the B RA Al-Wafi Panyileukan Bandung group with a total of 20 children. The technique of collecting data in this research is through observation, interviews and documentation. The results of data analysis showed that the ability of social interaction in Group B children RA Al-Wafi Panyileukan Bandung obtained an average value of 68 points, which was in the 60-69 interval with the sufficient category. Meanwhile, the emotional intelligence of Group B RA Al-Wafi Panyileukan Bandung children obtained an average value of 74, which is in the 70-79 interval with a good category.